Bioremediation Abilities of Antarctic Fungi - Martorell, María Martha; Ruberto, Lucas Adolfo Mauro; Castellanos, Lucia Ines; Mac Cormack, Walter Patricio
Cold environments represent a special challenge for life, even for the ubiquitous and metabolically versatile microorganisms. Therefore, bioremediation processes are hardly limited by low temperature. Most of the reported bioremediation-related information refers to temperate regions. However, during the last 20 years the research regarding such processes in cold environment has been reported for different cold regions all around the world, including the Alps, the Arctic, and Antarctica. Despite their amazing growth potential as well as enormous catabolic capabilities yeasts have been, among microorganisms, poorly studied as bioremediation tools.This book chapter focuses on one specifc extreme and permanently cold environment, Antarctica. General information on bioremediation and its use in cold environments is introduced. Also, the main contaminants in the Antarctic continent are summarized. For bioremediation in this continent, we propose, as a study case, the use of autochthonous yeasts with multiple bioremediation abilities, as they can be used to treat several sources of contamination in this region which is under a strong policy (Antarctic Protocol of Environmental Protection) related to management and environmental protection. Fil: Martorell, María Martha. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Ruberto, Lucas Adolfo Mauro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Nanobiotecnología. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Nanobiotecnología; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Castellanos, Lucia Ines. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - ...